2008
DOI: 10.1007/s00244-008-9225-3
|View full text |Cite
|
Sign up to set email alerts
|

Operative Modalities and Exposure to Pesticides During Open Field Treatments Among a Group of Agricultural Subcontractors

Abstract: This paper reports the results of a field study of occupational pesticide exposure (respiratory and dermal) among a group of Italian agricultural subcontractors. These workers consistently use pesticides during much of the year, thus resulting in a high exposure risk. Ten complete treatments were monitored during spring/summer. Pesticides that were applied included azinphos-methyl, dicamba, dimethoate, terbuthylazine, and alachlor. Several observations were made on worker operative modalities and the use of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 17 publications
1
29
0
1
Order By: Relevance
“…The study was conducted on 11 rice and 13 maize farms in Lombardy (Italy), which had a small number of workers (3 or 4), and participated in the study with one worker only, who was in charge for pesticides application. Since the main route of pesticide absorption is cutaneous (3537), the exposure was assessed by using pads (skin exposure) and by washing workers' hands at the end of the working shift with 200 ml of iso-propanol. The hand wash liquid was collected for analysis (hand skin exposure) according to the Organization for Economic Cooperation and Development (OECD) guidelines (38).…”
Section: Pesticide Risk Assessmentmentioning
confidence: 99%
“…The study was conducted on 11 rice and 13 maize farms in Lombardy (Italy), which had a small number of workers (3 or 4), and participated in the study with one worker only, who was in charge for pesticides application. Since the main route of pesticide absorption is cutaneous (3537), the exposure was assessed by using pads (skin exposure) and by washing workers' hands at the end of the working shift with 200 ml of iso-propanol. The hand wash liquid was collected for analysis (hand skin exposure) according to the Organization for Economic Cooperation and Development (OECD) guidelines (38).…”
Section: Pesticide Risk Assessmentmentioning
confidence: 99%
“…One study observed very little to no penetration through fabrics thicker than 0.8 mm, regardless of other factors [54], with workpants providing much greater protection than thinner work shirts [59], In addition, although garments made of both barrier and non-barrier fabrics have been shown to decrease dermal exposure [60], greater protection is afforded by waterproof polypropylene fabrics than by cotton garments [61]. For example, an Italian study found penetration through cotton clothing to range from 11.2% to 26.8%, whereas penetration through synthetic material was <2.4% [62], although a study of US citrus farmers found little difference between synthetic materials and woven garments [63].…”
Section: Ppe For Dermal Pesticide Exposurementioning
confidence: 99%
“…In addition, the protective features of PPE are dependent on proper use. For example, workers who roll their sleeves up or remove their gloves are at increased risk of dermal exposure [62].…”
Section: Ppe For Dermal Pesticide Exposurementioning
confidence: 99%
“…Concerning the ADE distribution, previous studies have shown similar results in which the hands and forearms are the most exposed body parts, and dermal exposure is the main contributor of the total exposure [68,69]. …”
Section: Discussionmentioning
confidence: 71%